Creative Tropical City: Mapping Darwin's Creative Industries - Lea, T.; Luckman, S.; Gibson, C.; Fitzpatrick, Donal; Brennan-Horley, C.; Willoughby-Smith, J.; Hughes, K. (School for Social and Policy Research, Charles Darwin University, 2009)
The Creative Tropical City: mapping Darwin's creative industries project is funded through the Australian government's Australian Research Council Linkage Project scheme, and is jointly supported by Darwin City Council, Tourism NT and the Northern Territory government's Department of the Chief Minister and Department of Natural Resources, Environment and the Arts. Each industry partner has an interest in pursuing new policies to enhance Darwin's creative industries, liveability and attractiveness to new migrants and existing residents. Specifically, the research project's three stated aims are: • to determine the nature, extent and change over time of the creative industries in Darwin • to interrogate the applicability of national and international creative industry policy frameworks to Darwin • to identify opportunities for transformation in the creative industries in Darwin. The methods used were: • interrogation of Australian Bureau of Statistics data • interrogation of data provided by our industrypartners • 98 one-on-one interviews, including a visual mapping exercise, with those who work in creative industries • literature reviews of the prolific creative industry literature written over the last decadereviews of existing policy frameworks • focus groups with representatives from creative industry sectors to discuss research findingsone-on-one interviews with key policy stakeholders • collaboration with creative industry practitioners to establish a policy feedback exhibition.